2017
DOI: 10.1016/j.celrep.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Caveolin-1 in Metastasis-Associated Macrophages Drives Lung Metastatic Growth through Increased Angiogenesis

Abstract: SummaryAlthough it is well established that tumor-associated macrophages take part in each step of cancer progression, less is known about the distinct role of the so-called metastasis-associated macrophages (MAMs) at the metastatic site. Previous studies reported that Caveolin-1 (Cav1) has both tumor-promoting and tumor-suppressive functions. However, the role of Cav1 in bone-marrow-derived cells is unknown. Here, we describe Cav1 as an anti-metastatic regulator in mouse models of lung and breast cancer pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 59 publications
(71 reference statements)
0
36
0
Order By: Relevance
“…Ang II receptor blockers (ARBs) are extensively used as anti-hypertensive drugs (9). Studies have reported that angiogenesis is essential for tumor progression and metastasis (10,11). Furthermore, studies have demonstrated that ARBs have the potential possibility to restrain the growth of several types of cancer cells (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Ang II receptor blockers (ARBs) are extensively used as anti-hypertensive drugs (9). Studies have reported that angiogenesis is essential for tumor progression and metastasis (10,11). Furthermore, studies have demonstrated that ARBs have the potential possibility to restrain the growth of several types of cancer cells (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…This was in line with a high percentage of VEGFR1 + cells found in liver metastasis patients, which correlated with worse patient outcome [100]. Conversely, a study found that calveolin-1 (Cav1) in MAMs restrains VEGF-A/VEGFR1 signaling; therefore, Cav1 depletion in MAMs promoted an increased metastatic growth and angiogenesis in lung metastatic tissue [101].…”
Section: Role Of Metastasis-associated Macrophages In Metastatic Progmentioning
confidence: 67%
“…Although these data should be verified in a larger case series and molecular studies, Cav-1 in the stromal component may be negatively correlated with that in BM of ADC. Recently, Cav-1 expression of fibroblast or macrophage in stromal component has been investigated in primary or secondary lung cancer [49][50][51].…”
Section: Discussionmentioning
confidence: 99%